GABA Signaling and Neuroactive Steroids in Adrenal Medullary Chromaffin Cells - Harada, Keita; Matsuoka, Hidetada; Fujihara, Hiroaki; Ueta, Yoichi; Yanagawa, Yuchio; Inoue, Masumi (Frontiers in Cellular Neuroscience, 2016)
GABA is produced not only in the brain, but also in endocrine cells by the two isoforms of glutamic acid decarboxylase (GAD), GAD65 and GAD67. In rat adrenal medullary chromaffin cells only GAD67 is expressed, and GABA is stored in large dense core vesicles, but not synaptic-like microvesicles. The 32/32 complex represents the majority of GABAA receptors expressed in rat and guinea pig chromaffin cells, whereas PC12 cells, an immortalized rat chromaffin cell line, express the 1 subunit as well as the 3. The expression of 3, but not 1, in PC12 cells is enhanced by glucocorticoid activity, which may be mediated by both the mineralocorticoid receptor and the glucocorticoid receptor. GABA has two actions mediated by GABAA receptors in chromaffin cells: it induces catecholamine secretion by itself and produces an inhibition of synaptically evoked secretion by a shunt effect. Allopregnanolone, a neuroactive steroid which is secreted from the adrenal cortex, produces a marked facilitation of GABAA receptor channel activity. Since there are no GABAergic nerve fibers in the adrenal medulla, GABA may function as a para/autocrine factor in the chromaffin cells. This function of GABA may be facilitated by expression of the immature isoforms of GAD and GABAA receptors and the lack of expression of plasma membrane GABA transporters. In this review, we will consider how the para/autocrine function of GABA is achieved, focusing on the structural and molecular mechanisms for GABA signaling.